Bovine Adenoviral Vector-Based Platform for Vaccine Development - Ekramy E. Sayedahmed; Vivek Gairola; Muralimanohara S. T. Murala; Suresh K. Mittal (Vaccines)
Adenoviral (AdV) vector-based vaccines employing the human AdV (HAdV) and chimpanzee AdV (ChAdV) vector platforms played a crucial role in combating the COVID-19 pandemic. However, the widespread use of these platforms, the prevalence of various HAdV types, and the resulting preexisting immunity have significantly impacted the vaccines utilizing these vector platforms. Considering these challenges, the bovine AdV type 3 (BAdV-3) vector system has emerged as a versatile and innovative platform for developing next-generation vaccines against infectious diseases. Inherent attributes like a high transduction efficiency, large transgene insertion capacity, broad tissue tropism, and robust induction of innate immunity add significant value to the BAdV vector platform for vaccine design. BAdV-3 vectors effectively elude HAdV-specific preexisting humoral and cellular immune responses. Additionally, BAdV-3 is low in pathogenicity for its host and is anticipated to be safe as a vaccine platform. This systematic review provides an overview of the development of BAdV-3 as a vaccine delivery platform and its application in designing vaccines for infectious agents of human and veterinary importance.